Enhancing rabbit farming efficiency with integrated genomics and nutritional strategies - Goswami, Naqash; Solomon Ahamba, Ifeanyi; Kinkpe, Lionel; Mujtaba Shah, Ali; Xiangyang, Ye; Song, Bing; Dong, Xianggui; Wang, Shuhui; Ren, Zhanjun (Frontiers in Animal Science, 2025)
Rabbit farming plays a crucial role in meeting the global demand for high-quality meat and sustainable agricultural practices. In recent years, significant attention has been directed toward the integration of Genomic-Assisted Selection (GAS) and Precision Nutrition (PN) as synergistic strategies to improve productivity and animal welfare in rabbit production systems. This integration is particularly critical given the intricate interplay between genetic predispositions and nutritional demands in optimizing rabbit farming outcomes. The present review systematically explores the genetic diversity inherent to rabbit breeds, examines the impact of key genetic traits on productivity and welfare metrics, and highlights advancements in genomic research and associated tools within the context of rabbit breeding practices. By examining the importance of personalized nutrition tailored to individual rabbit requirements, as well as nutritional strategies to optimize productivity and longevity. In this regard, we provide essential understanding for farmers and researchers in the rabbit farming industry. Our goal is to provide a new perspective on the significance of this integrated approach and its implications for future practices and research in rabbit production, emphasizing the need for continued efforts to harness the full potential of genomics and nutrition in enhancing rabbit farming practices.